Perubahan Karakter Pengangguran di Era Digital Tantangan dan Implikasi Kebijakan Untuk Pertumbuhan Inklusif - Syahbani, Rafli; Dyas, Azhalia; Arinda. P, Nabilla; Rayi. E, Syafa’; Revalina, Aisyah; Kusuma, Airlangga Surya (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of the digital era has brought significant changes to the labor market dynamics, including the characteristics of unemployment in Indonesia. Digitization creates new opportunities as well as complex challenges, especially for individuals who do not yet possess adequate technological skills. This research aims to analyze the changing character of unemployment in the digital age, with a focus on the phenomenon of internships as a company strategy in reducing operational costs and its impact on labor welfare. Through a qualitative approach based on the literature study, it was found that modern apprenticeship systems often do not provide permanent employment guarantees, creating risks of precarity for the young workforce. Additionally, inequality of access to digital training and technology education widens the skills gap between workers. The study highlights the importance of formulating more adaptive and inclusive policies to respond to the challenges of the digital age, including protecting the rights of apprenticeship workers, strengthening digital literacy, and improving access to skills training. Thus, inclusive economic growth can be achieved.